2007
DOI: 10.1641/b571106
|View full text |Cite
|
Sign up to set email alerts
|

Potential Impacts of Climate Change on the Distribution of North American Trees

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
310
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 412 publications
(331 citation statements)
references
References 59 publications
(45 reference statements)
14
310
3
4
Order By: Relevance
“…Annual temperature increases exceeding 1.5 °C are projected to result in a warming of 4-11 °C by the end of this century, with little concomitant increase in precipitation 1 . At this pace, climate zones will shift northward at a greater speed than trees can migrate 3 . To understand how future populations of forest trees may respond to climate change, it is essential to uncover past and present signatures of molecular adaptation in their genomes.…”
mentioning
confidence: 99%
“…Annual temperature increases exceeding 1.5 °C are projected to result in a warming of 4-11 °C by the end of this century, with little concomitant increase in precipitation 1 . At this pace, climate zones will shift northward at a greater speed than trees can migrate 3 . To understand how future populations of forest trees may respond to climate change, it is essential to uncover past and present signatures of molecular adaptation in their genomes.…”
mentioning
confidence: 99%
“…The large majority of recent studies on climate change impacts have therefore focused on the estimation of the shifts in species ranges that are expected according to different climatic and land use scenarios. These studies are mainly based on species distribution modelling and are employed in order to forecast changes in the distribution of single species Araujo et al, 2006;Beaumont et al, 2007;Huntley et al, 2007;McKenney et al, 2007;Lawler et al, 2009), ecosystems (Berry et al, 2003;Thuiller et al, 2006) or biodiversity (Bakkenes et al, 2002;Thuiller et al, 2005;Dormann et al, 2008). These techniques allow forecasting changes and are therefore important tools for current conservation planning in order to mitigate the impacts of climate and land use change on biodiversity .…”
Section: Introductionmentioning
confidence: 99%
“…Berteaux et al (2010) predicted a northward shift of isotherms, ranging from 240 km for the 5°C isotherm to 650 km for the -5°C isotherm, from their current positions by 2071 to 2100 in Quebec. McKenney et al (2007) suggested a displacements of favourable climate conditions more than 700 km, corresponding with an average decrease by 12% for the distribution areas of 130 species in North America. However, the models used to predict these climate envelops shifts considered neither the other environmental requirements of the species (edaphic conditions) nor the ecological processes that might interfere with the climate (such as competition).…”
Section: Migration Of Climate Niches For the Principal Tree Speciesmentioning
confidence: 99%